Self-Reported Basic Oral Health Knowledge of Primary School Students and Teachers in Rural Areas of Saudi Arabia - Shaheen R; AlShulayyil M; Baseer MA; Saeed Bahamid AA; AlSaffan AD; Al Herbisch R (Dove Medical Press, 2021)
Rakan Shaheen,1 Mohammed AlShulayyil,2 Mohammad Abdul Baseer,1 Ahmed Abdullah Saeed Bahamid,1 Abdulrahman Dahham AlSaffan,1 Reem Al Herbisch3 1Department of Preventive Dentistry, College of Dentistry, Riyadh Elm University, Riyadh, Saudi Arabia; 2Ministry of Health Hospital, Wadi Ad-Dawasir, Saudi Arabia; 3College of Dentistry, Riyadh Elm University, Riyadh, Saudi ArabiaCorrespondence: Mohammad Abdul BaseerDepartment of Preventive Dentistry, College of Dentistry, Riyadh Elm University, Namuthajiya Campus, Post Box No. 84891, Riyadh, 11681, Saudi ArabiaEmail ma_baseer@riyadh.edu.saBackground: Oral health knowledge is essential for establishing healthy behaviors.Aim: The purpose of the study was to determine and compare the basic oral health knowledge of 3- 6th grade government primary school students and teachers in rural areas of Saudi Arabia.Methods: A cross-sectional study was conducted among government primary school students and teachers in a rural area (Thadig and Ad-Delam) of the Riyadh region of Saudi Arabia using validated, structured, close-ended and self-administered questionnaires. The questionnaire comprised demographic variables and 18 multiple-choice items. A convenience sampling methodology was employed to select the study sample.Results: A total of 1864 subjects from rural area government primary schools [students (N = 1538) and teachers (N = 326)] participated in this study. The majority of the students were females 841 (54.7%), Saudi nationals 1376 (89.5%), and studying in 5th grade 446 (29%). Most teacher participants were females, 199 (61.0%), and Saudi nationals, 326 (100.0%). Teachers (12.62 ± 2.36) demonstrated significantly higher overall mean knowledge scores compared to the students (9.63 ± 2.36) (p < 0.001). Females and non-Saudi students showed significantly higher mean knowledge scores compared to their counterparts. However, 4th standard students showed significantly lower mean knowledge scores compared to other graders. Female teachers (13.17 ± 2.25) demonstrated significantly higher overall oral health knowledge scores compared to male teachers (11.75 ± 2.26) (p < 0.001).Conclusion: Basic oral health knowledge was adequate among 3- 6th grade government primary school students and teachers in rural areas of the Riyadh region.Keywords: oral health, knowledge, rural, students, teachers